Absolute Quantification of Isoflavones in the Flowers of Pueraria lobata by qHNMR - Punam Thapa; Hye Mi Kim; Joon-Pyo Hong; Ranhee Kim; Sunil Babu Paudel; Hyukjae Choi; Dae Sik Jang; Joo-Won Nam (Plants, 2022)
Pueraria lobata (Willd.) Ohwi. is a widely used medicinal plant in Korea, China, and Japan. The flower of P. lobata (Puerariae Flos) contains various bioactive substances such as triterpenoidal saponins and isoflavonoids. In this study, we developed a quantitative analysis of the isoflavones of Puerariae Flos by quantitative proton nuclear magnetic resonance (qHNMR) spectroscopy using the internal calibrant (IC). From the qHNMR results, the isoflavone content was found to be 7.99% and 10.57% for the MeOH sonication extract (PLs) and the MeOH reflux extract (PLr) of Puerariae Flos, respectively. The quantified isoflavone content was validated using the conventional analytical method, high-performance liquid chromatography with ultraviolet detection (HPLC-UV). The present study shows that validated qHNMR spectroscopy is a reliable method for quantifying and standardizing the isoflavone content in Puerariae Flos.